Pengujian Efektivitas Starter Jamur Beauveria bassiana terhadap Mortalitas Hypothenemus hampei - Kusnadi Kusnadi; Yayan Sanjaya (Jurnal Perlindungan Tanaman Indonesia, 2003)
An experiment concerning to the production of B. bassiana starter had been conducted to facilitate its use to the farmers. The production of starter was conducted by using maize rice mill as the growing medium of B. bassiana. To examine the effectiveness of the starter, it tested to H. hampei in vitro. The result showed that isolate of B. bassiana from Garut applied at 50 g/ml was the most effective to cause mortality of H. hampei. The percentage H. hampei mortality caused by this trial attained to 76 %.